Gamma‐glutamyl transferase predicts future stroke: A Korean nationwide study. Issue 2 (10th February 2018) - Yang, Wookjin; Kim, Chi Kyung; Kim, Do Yeon; Jeong, Han‐Gil; Lee, Seung‐Hoon
Abstract : Objective: Although gamma‐glutamyl transferase (GGT) is generally regarded as an alternative biomarker for alcohol consumption, its independent role in vascular diseases emerged recently. However, its role in stroke remains unknown. The aim of this study is to clarify the impact of GGT on stroke in a large‐sized, national, standardized population cohort in Korea. Methods: In Korea, the National Health Insurance Service (NHIS) provides full‐coverage health insurance service for all citizens. Using data from the NHIS, the NHIS–National Sample Cohort was designed by randomly selecting 2% of Koreans, carefully considering demographic characteristics. We analyzed eligible individuals from this standardized cohort. The Cox proportional hazards model was used for the study investigating the relationship between GGT and stroke. Results: Among the 456, 100 eligible participants, 7, 459 patients (1.64%) developed stroke as follows: 5, 789 ischemic strokes, 1, 046 intracerebral hemorrhages (ICHs), and 624 subarachnoid hemorrhages. GGT was independently correlated with increased risk of stroke after adjustment for alcohol consumption and stroke risk factors (hazard ratio [HR] = 1.39, 95% confidence interval [CI] = 1.29–1.51). The risks of both ischemic stroke (HR = 1.45, 95% CI = 1.32–1.58) and ICH (HR = 1.46, 95% CI = 1.18–1.80) were significantly elevated with increasing GGT. Despite some effect modifications by sex, age, and alcohol, the risk of total stroke and ischemic stroke in association with GGT remained significant in all subgroups. Interpretation: In a standard Korean population, GGT was a novel biomarker predicting stroke risk, independently from alcohol consumption and other risk factors. Ann Neurol 2018;83:375–386